2017
DOI: 10.3390/nu9070782
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Nutritive Value of Low-Price Model Lunch Sets Provided to Garment Workers in Cambodia

Abstract: Background: The establishment of staff canteens is expected to improve the nutritional situation of Cambodian garment workers. The objective of this study is to assess the nutritive value of low-price model lunch sets provided at a garment factory in Phnom Penh, Cambodia. Methods: Exemplary lunch sets were served to female workers through a temporary canteen at a garment factory in Phnom Penh. Dish samples were collected repeatedly to examine mean serving sizes of individual ingredients. Food composition table… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…In a previous research in Cambodia, a canteen offering low-price lunches ($1.00 USD) demonstrated potential to improve the food security of RMG workers. 22,23 The study assessed the nutritive value of a low-price lunch model and showed that the lunches satisfied energy and macronutrient recommendations but did not have enough iron. If meals are provided, attention to the quality and diversity of food is important to make health and productivity improvements.…”
Section: Discussion and Implications For Programs And Policiesmentioning
confidence: 99%
“…In a previous research in Cambodia, a canteen offering low-price lunches ($1.00 USD) demonstrated potential to improve the food security of RMG workers. 22,23 The study assessed the nutritive value of a low-price lunch model and showed that the lunches satisfied energy and macronutrient recommendations but did not have enough iron. If meals are provided, attention to the quality and diversity of food is important to make health and productivity improvements.…”
Section: Discussion and Implications For Programs And Policiesmentioning
confidence: 99%
“…A temporary canteen was installed in a roofed outdoor area at the factory site [18]. Apsara Garment Co. Ltd. had never operated a staff canteen before.…”
Section: Interventionmentioning
confidence: 99%
“…Sets should provide about one third of the recommended dietary allowance (RDA) for non-pregnant women aged 19-30 years old (total~700 kcal) [20]. Based on these standards, a biweekly menu (of 12 model lunch sets) was outlined in consultation with the caterer [18]. Focus was laid on accepted Cambodian dishes, using local foods and ensuring variety by providing cereals, various vegetables, animal source foods (meat or fish), and fresh fruits on a daily basis.…”
Section: Interventionmentioning
confidence: 99%
See 2 more Smart Citations